2020
DOI: 10.3897/rrpharmacology.6.53649
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B from antifungal to antiviral therapy: promising modern therapeutic branch

Abstract: Introduction: Amphotericin B (AmB) which belongs to the polyene group has a wide spectrum in vitro and in vivo antimicrobial activity against fungi and parasites, but resistance to AmB is rare despite extensive use. Material and methods: Atotal of 2530 articles were investigated in PubMed (n = 1525), Medline (n = 705), and Google Scholar (n = 300). From 2530 articles, only 61 studies were included in this review. All the short and full articles were searched that were scheduled to be published until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…A considerably greater amount of IL-12 was produced in patients with mild COVID-19 during the beginning of the acute phase due to SARS-CoV-2 infection than in patients with moderate or severe symptoms and healthy controls. Interestingly, multiple investigations found that patients with severe COVID-19 had much fewer peripheral NK cells than healthy people [ 23 , 24 ], or people who have COVID-19 minor cases [ 25 ]. IL-12 induction is necessary to sustain NK cell numbers in the early stages of SARS-CoV-2 infection and this may contribute to the evasion of viral propagation seen in asymptomatic and mildly symptomatic patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A considerably greater amount of IL-12 was produced in patients with mild COVID-19 during the beginning of the acute phase due to SARS-CoV-2 infection than in patients with moderate or severe symptoms and healthy controls. Interestingly, multiple investigations found that patients with severe COVID-19 had much fewer peripheral NK cells than healthy people [ 23 , 24 ], or people who have COVID-19 minor cases [ 25 ]. IL-12 induction is necessary to sustain NK cell numbers in the early stages of SARS-CoV-2 infection and this may contribute to the evasion of viral propagation seen in asymptomatic and mildly symptomatic patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This resistance can delay and impede treatment, leading to complications or death [10,11]. As well as, the adverse effects associated with these drugs [12,13]. Besides, a patient may need more care, as well as the use of alternative and more expensive antibiotics, which may have more severe side effects or may require more invasive treatments to be given in hospitals, such as intravenous injection [9,14,15].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%
“…Amphotericin B (AmB) is a broad-spectrum antifungal that remains the major fungicidal drug for treating serious systemic mycotic infections (Obayes, 2020 ). Despite its therapeutic benefits, AmB has several adverse effects on the kidney that limit treatment continuation (Goyal et al, 2020 , Salehzadeh et al, 2020 , Gursoy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%